Intervensi Edukasi Tuberkulosis: Meningkatkan Pengetahuan Menjadi Tindakan Pencegahan Pada Petugas PPSU Di Jakarta Barat - Machrumnizar Machrumnizar; Yuliana Yuliana; Arleen Devita; Hans Sutanto Utama (CV. Multi Kreasi Media, 2025)
The high burden of tuberculosis (TB) in Indonesia is still a public health problem, including in West Jakarta. The role of public infrastructure and facilities (PPSU) officers in the field plays an important role in maintaining the cleanliness of the urban environment. They are a group that is vulnerable to exposure to infectious diseases such as TB. Appropriate education is needed to transform knowledge into real action in preventing TB, so it is necessary to improve knowledge and TB prevention actions in PPSU officers through educational intervention programs. The population of community service activities (PKM) are PPSU officers in West Jakarta, which is an area with a high incidence of TB. Education uses a socialization design through counseling related to TB, including transmission, symptoms, and prevention steps. Educational media using posters, brochures, and videos. Interactive training by providing simulations of TB prevention practices such as the use of masks and cough etiquette. The increase in participant knowledge is evaluated based on pre-test and post-test scores. Participants with good scores during the pre-test 24.6% became 87% in the post-test. The change in pre-test and post-test scores was significant with a p value <0.05. The educational intervention program was effective in increasing the capacity of PPSU as TB prevention agents in their work environment. The results indicate the importance of implementing similar programs continuously to maintain the health of field workers to strengthen TB awareness and preventive actions in high-risk areas.